Vitamin D supplementation to prevent tuberculosis infection in South African schoolchildren: multicenter phase 3 double-blind randomized placebo-controlled trial (ViDiKids) - Keren Middelkoop; Justine Stewart; Neil Walker; Carmen Delport; David A. Jolliffe; Anna K. Coussens; James Nuttall; Jonathan C.Y. Tang; William D. Fraser; Christopher J. Griffiths; Geeta Trilok Kumar; Suzanne Filteau; et al. (International Journal of Infectious Diseases, 2023)
ABSTRACT: Objectives: To determine whether weekly oral supplementation with 10,000 IU vitamin D3 for 3 years reduces the risk of sensitization to M. tuberculosis in South African schoolchildren aged 6-11 years with negative QuantiFERON-tuberculosis (TB) Gold Plus (QFT-Plus) assay results at baseline. Methods: We conducted a phase 3 randomized placebo-controlled trial in 1682 children attending 23 primary schools in Cape Town. The primary outcome was a positive end-trial QFT-Plus result, analyzed using a mixed effects logistic regression model with the school of attendance included as a random effect. Results: 829 vs. 853 QFT-Plus-negative children were randomized to receive vitamin D3 vs. placebo, respectively. Mean end-study 25(OH)D concentrations in participants randomized to vitamin D vs. placebo were 104.3 vs 64.7 nmol/l, respectively (95% confidence interval for difference, 37.6 to 41.9 nmol/l). A total of 76/667 (11.4%) participants allocated to vitamin D vs. 89/687 (13.0%) participants allocated to placebo tested QFT-Plus positive at 3-year follow-up (adjusted odds ratio 0.86, 95% confidence interval 0.62-1.19, P = 0.35). Conclusion: Weekly oral supplementation with 10,000 IU vitamin D3 for 3 years elevated serum 25(OH)D concentrations among QFT-Plus-negative Cape Town schoolchildren but did not reduce their risk of QFT-Plus conversion.